2008
DOI: 10.1098/rspb.2008.0560
|View full text |Cite
|
Sign up to set email alerts
|

When microbes and consumers determine the limiting nutrient of autotrophs: a theoretical analysis

Abstract: Ecological stoichiometry postulates that differential nutrient recycling of elements such as nitrogen and phosphorus by consumers can shift the element that limits plant growth. However, this hypothesis has so far considered the effect of consumers, mostly herbivores, out of their food-web context. Microbial decomposers are important components of food webs, and might prove as important as consumers in changing the availability of elements for plants. In this theoretical study, we investigate how decomposers d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
37
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 37 publications
(37 citation statements)
references
References 61 publications
0
37
0
Order By: Relevance
“…Although the presence of a 'consumer driven nutrient recycling' (CDNR) mechanism was established using pelagic herbivore-autotroph interactions, recent studies have shown a similar mechanism in microorganisms consuming both dissolved and particulate organic matter. A theoretical analysis demonstrated that through a CDNR-like recycling mechanism, terrestrial microorganisms can be more important than herbivores in determining the nutrient that limits autotrophic growth (Cherif and Loreau 2009). Due to the low amount of primary production that is consumed by herbivores in forest ecosystems, the role of a microbially driven recycling mechanism was hypothesized to be especially pronounced and promote P limitation due to relatively high biomass P in microbial decomposers (Cherif and Loreau 2009).…”
Section: Theoretical Basis For Biomass Stoichiometry and Nutrient Cycmentioning
confidence: 99%
See 2 more Smart Citations
“…Although the presence of a 'consumer driven nutrient recycling' (CDNR) mechanism was established using pelagic herbivore-autotroph interactions, recent studies have shown a similar mechanism in microorganisms consuming both dissolved and particulate organic matter. A theoretical analysis demonstrated that through a CDNR-like recycling mechanism, terrestrial microorganisms can be more important than herbivores in determining the nutrient that limits autotrophic growth (Cherif and Loreau 2009). Due to the low amount of primary production that is consumed by herbivores in forest ecosystems, the role of a microbially driven recycling mechanism was hypothesized to be especially pronounced and promote P limitation due to relatively high biomass P in microbial decomposers (Cherif and Loreau 2009).…”
Section: Theoretical Basis For Biomass Stoichiometry and Nutrient Cycmentioning
confidence: 99%
“…Due to the low amount of primary production that is consumed by herbivores in forest ecosystems, the role of a microbially driven recycling mechanism was hypothesized to be especially pronounced and promote P limitation due to relatively high biomass P in microbial decomposers (Cherif and Loreau 2009). Shifts in the limiting nutrient caused by differential retention and recycling by microorganisms due to differences in biomass stoichiometry can result in shifts in autotrophic community composition driving changes in ecosystem processes (for example, C acquisition) (Cherif and Loreau 2009). This mechanism was demonstrated empirically where the inclusion of a bacterial community switched nutrient limitation in an algal culture from N to P limitation (Danger and others 2007).…”
Section: Theoretical Basis For Biomass Stoichiometry and Nutrient Cycmentioning
confidence: 99%
See 1 more Smart Citation
“…By competing for dissolved nutrients and changing the relative availability of nutrients, bacteria can promote nutrient limitation of autotrophs (Cherif & Loreau 2009). Under certain circumstances, the influence of bacteria can cause changes in phytoplankton stoichiometry.…”
Section: Nutrient Limitation Patternsmentioning
confidence: 99%
“…Hence, the stoichiometry of a population probably differs from the stoichiometry of its individual components and might vary through time, a fact rarely considered (Nakazawa 2011). Life is complex: different organisms might show different strategies to regulate their elemental composition (Mitra & Flynn 2005, 2007; food webs are diverse, both horizontally (i.e., within the same trophic level) and vertically (i.e., across trophic levels). Predictions that apply to one trophic level may prove erroneous if they neglect other species from the same (Danger et al 2008) or from different trophic levels (Cherif & Loreau 2009). These additional The aim of this book is to provide an overview of the importance of stoichiometry in the biomedical field.…”
Section: Future Needs and Challenges Aheadmentioning
confidence: 99%